Social dynamics and structural coupling: two keys, yet often neglected, elements of community participation in Global Health projects - Muela Ribera , Joan (Revista de Antropología Social, 2023)
This article is a reflection on communities participating in Global Health projects that use Mass Drug Administration (MDA). Due to its complexity, community participation is widely recommended to adapt MDA interventions to the local contexts. However, evaluation of MDA projects focusses more on coverage and reasons for non-adherence as mentioned by project participants, than on the social dynamics that affect participation. In this article, I present part of the implementation research of two MDA projects carried out in The Gambia, emphasising how social structures, values and dynamics affected adherence. Finally, I argue that it is more relevant to couple the project with these structures and dynamics, than focusing on “fixing” adherence problems with information and health education strategies.